Thermophysical Reactivity Control of RBMK-1000; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Vorobiev A. V. Aleksandr Vladimirovich (2016, 2016)
Title screen